CLASSROOM MANAGEMENT AND TEACHER INTERVENTION CAN REDUCE STUDENT ANXIETY LEVELS - Ihsan Dacholfany, Muhammad; Retno W, Bayu; Havidotinnisa, Siti; Harini, Hegar (LP2M IAI Al-Khairat Pamekasan, 2023)
The purpose of this study was to find out the effectiveness of classroom management and teacher intervention in reducing students' anxiety levels at school. The researcher used a qualitative research method with descriptive research. The steps in this research were to collect information or collect classification data, and then perform data analysis, interpretation, and make conclusions and reports. The research was carried out from January 13 to February 14, 2023. The results of the research the researchers conducted showed that anxiety in students can be reduced through good classroom management in several ways, namely through preventive efforts by motivating students to concentrate on lessons and conditioning students to be ready to learn in class; readiness to learn greatly determines student learning activities. Besides these preventive efforts to reduce student anxiety in class in a curative way, this method requires the role of the guidance and counseling teacher by providing counseling to students who have high anxiety using systematic desensitization techniques.